Time series forecasting of greater one-horned rhinoceros poaching levels at Kaziranga National Park, Assam, India - Saureesh Das; Rashmi Bhardwaj (Pachyderm)
This paper deals with the forecasting of poaching of the greater one-horned rhinoceros (Rhinoceros unicornis) (GOH) at Kaziranga National Park (KNP or the Park), Assam, India. Instances of poaching adversely affect efforts to conserve and increase the rhino population of the Park. The time series of total instances of poaching of GOH at KNP from the year 1965–2019 was considered in the study. The information about the period ending 2015 was used as training and testing data, and poaching levels for the period 2016–2019 were predicted using three different forecasting methods and compared with the available actual data. Three methods of time series forecasting are compared, namely Holt’s method (HM), Holt–Winters’ multiplicative method (HWMM) and Holt–Winters’ additive method (HWAM).